Effects of BrMYC2/3/4 on Plant Development, Glucosinolate Metabolism, and Sclerotinia sclerotiorum Resistance in Transgenic Arabidopsis thaliana - Teng, Zhiyan; Zheng, Weiwei; Yu, Youjian; Hong, Seung-Beom; Zhu, Zhujun; Zang, Yunxiang (Frontiers in Plant Science, 2021)
MYC2/3/4, known as a basic helix-loop-helix (bHLH) transcription factor, directly activate the genes involved in diverse plant development and secondary metabolites biosynthesis. In this study, we identified and cloned five MYC paralogs (BrMYC2/3-1/3-2/4-1/4-2) from Chinese cabbage (Brassica rapa ssp. pekinensis). In-silico analyses for the physicochemical properties suggested that BrMYC2/3-1/3-2/4-2/4-3 are unstable hydrophobic and acidic proteins, while BrMYC4-1 is an unstable hydrophobic and basic protein. Domain prediction analysis showed that BrMYC2/3/4 belong to the bHLH superfamily and are closely related to AthMYC2/3/4 orthologs that mediate the regulation of various secondary metabolites. When expressed in Arabidopsis under the control of 35S promoter, each of the BrMYC2/3-1/3-2/4-1/4-2 transgenes differentially influenced root and shoot elongation, vegetative phase change, flowering time, plant height and tiller number after flowering, and seed production. Despite the variation of phenotypes between the transgenic lines, all the lines except for BrMYC4-2 exhibited shorter seed length, less seed weight, higher accumulation of glucosinolates (GSs) and resistance to S. sclerotiorum than control. Notably, BrMYC2 overexpression line significantly reduced the lengths of root and hypocotyl, seed length and weight, along with faster bolting time and strikingly higher accumulation of total GSs. Accumulation of GSs at the highest levels in the BrMYC2 line conferred the highest resistance to S. sclerotiorum. Unlike BrMYC3 and BrMYC4, BrMYC2 stimulated the growth of plant height after fluorescence. The results of this study point to the BrMYC2 overexpression that may provide the beneficial effect on plant growth and development via plant resistance to the fungal pathogen.